The political economy of EDP fiscal forecasts: an empirical assessment - Pina, Álvaro (2010)
This paper analyses the track record of fiscal forecasts reported by 15 European countries in the context of the Excessive Deficit Procedure. For the budget balance, gross fixed capital formation (GFCF) and interest payments, we study the statistical properties of forecast errors and their politico-institutional determinants. While errors in interest and GFCF expenditure present few systematic patterns, budget balance errors are responsive to fiscal institutions and to opportunistic motivations, especially from 1999 onwards: upcoming elections induce over-optimism, whereas commitment or mixed forms of fiscal governance and numerical expenditure rules (but not deficit and debt rules) are associated to greater prudence.